Role of Inhalant and Food Allergens in Child Sensitization: A Prospective Study in 176 Children - Arnaldo Cantani (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2015)
Background: The origin of atopic disease is poly factorial and the development of atopic manifestations appears to be linked to interactions between genetic and environmental factors. Such data seem to focus attention on the rising prevalence rates of atopic dermatitis, a common debilitating skin condition in infants and young children. They also often have asthma and/or allergic rhinitis. Patients and Methods: The aim of the present study was to evaluate the rate of SPT (skin prick tests) and RAST response to Der p in atopic children with AD. We have prospectively studied 176 children (93 males and 83 females) aged from 6 months to 7 years, and divided into four different groups, including controls. We studied also their family history in the accompanying parents Results. The data of the present study show that a significantly higher proportion of children with AD have positive SPTs to Der p than the controls, while RAST was positive in a lower proportion of babies. A significant part of the parents had a positive atopic history. Conclusion: The early onset of such disorders in different parts of the world, and the strict connection between cutaneous and respiratory atopy appear of primary importance. Consequently, there is the clinical imperative that effective strategies should be adopted to amplify and improve preventative measures in at high-risk (HR) babies.